Analytical and Computational Advances, Opportunities, and Challenges in Marine Organic Biogeochemistry in an Era of “Omics” - Steen, Andrew D.; Kusch, Stephanie; Abdulla, Hussain A.; Cakić, Nevenka; Coffinet, Sarah; Dittmar, Thorsten; Fulton, James M.; Galy, Valier; Hinrichs, Kai-Uwe; Ingalls, Anitra E.; Koch, Boris P.; Kujawinski, Elizabeth; et al. (Frontiers in Marine Science, 2020)
Advances in sampling tools, analytical methods and data handling capabilities have been fundamental to the growth of marine organic biogeochemistry over the past four decades. There has always been a strong feedback between analytical advances and scientific advances. However, whereas advances in analytical technology were often the driving force that made possible progress in elucidating the sources and fate of organic matter in the ocean in the first decades of marine organic biogeochemistry, today process-based scientific questions should drive analytical developments. There are several paradigm shifts and challenges for the future that are related to the intersection between analytical progress and scientific evolution. Untargeted “molecular headhunting” for its own sake is now being subsumed into process-driven targeted investigations that ask new questions and thus require new analytical capabilities. However, there are still major gaps in characterizing the chemical composition and biochemical behavior of macromolecules. Field-based measurements are now routinely complemented by controlled laboratory experiments and in-situ rate measurements of key biogeochemical processes. And finally, the multidisciplinary investigations that are becoming more common generate large and diverse datasets, requiring innovative computational tools to integrate often disparate data sets, including better global coverage and mapping. Here, we compile examples of developments in analytical methods that have made possible transformative advances over the past decade, and we project some challenges and opportunities for the future to insure continued progress in understanding the cycling of organic carbon in the ocean.